2017
DOI: 10.14710/jitaa.42.3.160-166
|View full text |Cite
|
Sign up to set email alerts
|

Breeding value of sires based on offspring weaning weight as a recommendation for selecting Kebumen Ongole Grade cattle

Abstract: The objective of study was to estimate breeding value of sires of Kebumen Ongole grade cattle based on offsprings weaning weight. This research was carried out from August to December 2015 in Urut Sewu area, Kebumen. The calculation of genetic parameter estimation was heritability of weaning weight. The value of heritability was used to calculate the breeding value of sires based on offsprings weaning weight. Heritability was calculated using paternal half-sib correlation with the direct pattern variance analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…The results of this study were also higher than the results reported by Ikhsanuddin et al [9] that in Aceh cattle BW was 13.66 ± 1.08 kg, WW was 71.60 ± 7.92 kg (205 days old), and YW was 104.66 ± 11.72 kg (365 days old). However, the WW and YW of OG cattle of this study were not much different from the results of research of Prihandini et al [10] who reported that WW and YW of OG cattle were 109.10 ± 18.35 kg and 132.70 ± 19.93 kg, respectively, and from the result of research of Sumadi et al [11,12] who reported that WW of Ongole Grade cattle in Kebumen was 119.40 ± 36.61 kg.…”
Section: Resultscontrasting
confidence: 88%
“…The results of this study were also higher than the results reported by Ikhsanuddin et al [9] that in Aceh cattle BW was 13.66 ± 1.08 kg, WW was 71.60 ± 7.92 kg (205 days old), and YW was 104.66 ± 11.72 kg (365 days old). However, the WW and YW of OG cattle of this study were not much different from the results of research of Prihandini et al [10] who reported that WW and YW of OG cattle were 109.10 ± 18.35 kg and 132.70 ± 19.93 kg, respectively, and from the result of research of Sumadi et al [11,12] who reported that WW of Ongole Grade cattle in Kebumen was 119.40 ± 36.61 kg.…”
Section: Resultscontrasting
confidence: 88%
“…Recent studies on genetics and breeding of Ongole Grade cattle explores various aspects like genetic relationship (Hartatik et al 2017;Hartatik et al 2018), heritability of body size (Paputungan et al 2015) and breeding value estimating of sire superiority (Sumadi et al 2017). But, the genetic diversity of Ongole Grade cattle is rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hardjosubroto (1994) if a livestock has a high BV then the livestock will have a high potential that can be inherited to the offspring. Several previous studies showed the higher BV in Kebumen Ongole Grade (KOG), Sumba Ongole (SO), Ongole crossbreed (PO) and Nalore cattle were 49.76 kg, 66.05 kg, 45.96 and 20.75 kg respectively (Sumadi et al ., 2017;Said et al, 2016;Paputungan et al, 2015;Rodriguez and Guerra, 2013). The magnitude of a male's performance can be estimated by breeding value (BV) so that cattle with high growth potential result in continuity of selection program.…”
Section: Heritability Valuementioning
confidence: 99%